1997
DOI: 10.1182/blood.v90.2.526
|View full text |Cite
|
Sign up to set email alerts
|

The Ig Heavy Chain Gene Is Frequently Involved in Chromosomal Translocations in Multiple Myeloma and Plasma Cell Leukemia as Detected by In Situ Hybridization

Abstract: Chromosome rearrangement of 14q32.33 has recurrently occurred with variable partner sites, including 11q13.3, 8q24.1, 18q21.3, and 6p21.1 in multiple myeloma (MM). To assess the actual incidence of 14q32.33 translocation and to elucidate its implication in the pathogenesis of MM, we studied 42 patients with MM, plasma cell leukemia, or plasmacytoma and 5 with monoclonal gammopathy with undetermined significance (MGUS) by G-banding and molecular cytogenetic methods. Using double-color fluorescence in situ hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(55 citation statements)
references
References 44 publications
2
53
0
Order By: Relevance
“…A positive C‐MYC status was found in six of six cases (100%) with a cBL morphology and in 10 of 18 cases (55.6%) with a aBL morphology, but also in nine of 15 cases (60%) with a DLBCL morphology. In summary, C‐MYC rearrangement was found to be an invariable feature of cBL and highly characteristic, but not specific for BL, confirming previous reports (Sigaux et al , 1984; De Jong et al , 1988; Thangavelu et al , 1990; Ladanyi et al , 1991; Nishida et al , 1997; Kramer et al , 1998; Akasaka et al , 2000; Nakamura et al , 2002; Barth et al , 2004; Mauch et al , 2004; Haralambieva et al , 2005).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A positive C‐MYC status was found in six of six cases (100%) with a cBL morphology and in 10 of 18 cases (55.6%) with a aBL morphology, but also in nine of 15 cases (60%) with a DLBCL morphology. In summary, C‐MYC rearrangement was found to be an invariable feature of cBL and highly characteristic, but not specific for BL, confirming previous reports (Sigaux et al , 1984; De Jong et al , 1988; Thangavelu et al , 1990; Ladanyi et al , 1991; Nishida et al , 1997; Kramer et al , 1998; Akasaka et al , 2000; Nakamura et al , 2002; Barth et al , 2004; Mauch et al , 2004; Haralambieva et al , 2005).…”
Section: Resultssupporting
confidence: 88%
“…BL characteristically carry a reciprocal translocation t(8;14)(q24;q32) or one of its variants resulting in the deregulation of the C‐MYC proto‐oncogene (Dalla‐Favera et al , 1982; Hecht & Aster, 2000). However, this molecular marker is not specific for BL, as it is also detected in approximately 15% of DLBCL as well as in secondary precursor B‐lymphoblastic leukaemia/lymphoma, aggressive lymphoma secondary to follicular lymphoma, and in some cases of multiple myeloma (Sigaux et al , 1984; De Jong et al , 1988; Thangavelu et al , 1990; Ladanyi et al , 1991; Nishida et al , 1997; Kramer et al , 1998; Akasaka et al , 2000; Nakamura et al , 2002; Barth et al , 2004; Mauch et al , 2004; Haralambieva et al , 2005). Thus, a clear‐cut definition of BL and its delimitation from DLBCL is blurred, leaving the pathologist with the open question of how to classify highly proliferative peripheral blastic B‐cell lymphoma (HPBCL) with some but not all features of BL and, even more irritatingly, leaving the clinician with the unsolved problem of how to treat these patients.…”
mentioning
confidence: 99%
“…As PCL is a tumor of PCs, which have undergone the processes of somatic hypermutation and isotype switch recombination in germinal centers, the translocations may have occurred during the recombination of switch regions in isotype switching. It was reported that IgH translocations are present in about 80% patients with PCL detected by interphase FISH (Nishida et al. , 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Whether STs are an early oncogenic change, a late ‘trigger’ of disease progression or a non‐pathogenic marker of genetic instability has been an interesting question with important implications on our understanding of myeloma pathogenesis. If STs are oncogenic, their presence in 50–75% of primary MM tumours (Nishida et al ., 1997; Avet‐Loiseau et al ., 1998; Sawyer et al ., 1998; Ho et al ., 2001) and the heterogeneity of chromosomal partners and partner oncogenes would imply that STs cannot be the only oncogenic factor, and a number of mechanisms must be involved. This heterogeneity was proposed as one of the arguments against STs being a unifying oncogenic change (Avet‐Loiseau et al ., 1998).…”
Section: Switch Translocations – Implications For Pathogenesis?mentioning
confidence: 99%